Pengaruh Model Cooperative Learning Terhadap Perkembangan Bahasa Anak Speech Delay Di PAUD Fathur Rahman - Khoiryah Nabila Putri; Ghalidza Annisa Haq; Asri Dwi Puspita (Khirani: Jurnal Pendidikan Anak Usia Dini, 2024)
This research discusses the influence of cooperative learning models on the language development of children with speech delay. The aim of this study is to examine and demonstrate the effectiveness of the cooperative learning model in improving the speaking abilities of children with speech delay. This research utilizes a descriptive qualitative approach with qualitative questionnaire methods, participatory observation, and structured interviews. Subject determination in the research uses purposive sampling techniques. The research findings indicate that the cooperative learning model can be used as one of the models implemented by teachers to address children with speech delay in schools. The series of learning processes, consisting of three main types of activities arranged by teachers every day, provide opportunities for children with speech delay to socialize intensively with their peers at school, thereby stimulating every aspect of cognitive, affective, and psychomotor development in students effectively.